DETERMINAN FACTORS INFLUENCING PATIENT SAFETY INCIDENT REPORTING: STUDY IN THE INPATIENT UNIT OF REGIONAL HOSPITAL IN INDONESIA - Puji, Lela Kania Rahsa; Nanggonman, Richard Devirson; Indah, Fenita Purnama Sari; Faizal, Doddy; Melia, Riska Edwi (Indonesian Journal of Health Science, 2025)
Reporting Patient Safety Incidents (PSI) is a crucial component in improving healthcare quality and preventing adverse events. However, the rate of PSI reporting in Indonesia remains relatively low. Bunda Sejati Hospital has shown an increasing trend in reported incidents, but the influencing factors behind this reporting are not yet fully understood. This study aims to identify the factors associated with the reporting of patient safety incidents in the Inpatient Unit of Bunda Sejati Hospital. This research is an analytical study with a quantitative approach and cross-sectional design. The population consisted of all 32 nurses in the Inpatient Unit of Bunda Sejati Hospital. Data were collected using a questionnaire, and data analysis was performed using the chi-square test. The results showed significant relationships between knowledge (p=0.001), reporting/feedback response (p=0.006), patient safety culture (p=0.006), leadership (p=0.006), reward (p=0.000), and training (p=0.002) with the reporting of patient safety incidents. Knowledge, reporting/feedback response, patient safety culture, leadership, reward, and training are significantly associated with the reporting of patient safety incidents. Improving these factors is expected to encourage a stronger reporting culture and enhance patient safety in hospitals